Advances in Smart Vehicular Technology, Transportation, Communication and Applications Proceeding of the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications, October 25-28, 2018 Mount Emei, China, Part 2 - Zhao, Yong.; Wu, Tsu-Yang.; Chang, Tang-Hsien.; Pan, Jeng-Shyang.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights papers presented at the Second International Conference on Smart Vehicular Technology, Transportation, Communication and Applications (VTCA 2018), which was held at Mount Emei, Sichuan Province, China from 25 to 28 October 2018. The conference was co-sponsored by Springer, Southwest Jiaotong University, Fujian University of Technology, Chang'an University, Shandong University of Science and Technology, Fujian Provincial Key Lab of Big Data Mining and Applications, and the National Demonstration Center for Experimental Electronic Information and Electrical Technology Education (Fujian University of Technology). The conference was intended as an international forum for researchers and professionals engaged in all areas of smart vehicular technology, vehicular transportation, vehicular communication, and applications.
Modified Adaptive Nonsmooth Attitude Tracking Control of Quadrotor UAV with Dynamic Uncertainties -- Geo-spatial Ontology Matching through Compact Evolutionary Algorithm -- Research on Optimization Of LMS Frequency Estimation Based On FPGA Technology -- The Development and Analysis of Electromagnetic Compatibility for Vehicles -- Non-linear Random Change Differential Evolution for Multi-objective Resource Allocation Problem -- Design and Realization of Intelligent Voice-control Car based on Raspberry Pi -- Improved Performance of Wireless Sensor Network Based on Fuzzy Logic for Clustering Scheme -- Dynamic Traffic Information Estimation based on Floating Car Data -- Regional Coverage Monitoring Planning Technology for Multi-UAV Based on Pruning PSO -- Using On-Board Diagnostics Data to Analyze Driving Behavior and Fuel Consumption -- Application of TRIZ to determine strategies for Transitioning from Third-party to Fourth-party Logistics in China.
Keywords: Computational intelligence; Transportation engineering; Traffic engineering; Artificial intelligence; Computational Intelligence; Transportation Technology and Traffic Engineering; Artificial Intelligence